Evaluation Study on Employment Assurance Scheme - Planning Commission (Planning Commission, 2000)
"The Employment Assurance Scheme was launched on 2nd October, 1993 in 1778 identified backward blocks situated in drought prone, desert, tribal and hill areas where the revamped public distribution system was in operation. Subsequently, the scheme was extended to cover all the blocks by April, 1997. The primary objective of the Employment Assurance Scheme is to provide gainful employment in manual work during lean agricultural season to all able bodied adults in rural areas who are in need of work, but cannot find it. The secondary objective is the creation of economic infrastructure and community assets for sustained employment and development."
Programme Evaluation Organisation Planning Commission Government of India